Effect of adverse weather on neonatal caribou survival — a review - Miller, Frank L.; Gunn, Anne (Rangifer, 1986)
This paper reviews the relationship between adverse weather and neonatal caribou (Rangifer tarandus spp.) survival in North America by examining the available literature and our own findings. The viewpoint that adverse weather on the calving ground can result in major losses of newborn barren-ground caribou (R. t. groenlandicus) calves is largely unsupported. Published reports of calf mortality caused by adverse weather are questionable because causes of death were rarely determined by postmortem examinations. Circumstantial evidence associated with the small samples of dead calves does not support published assumptions that the mortality was weather related, or that high losses due to adverse weather are common events. The applicability of results from physiological testing are questionable, because the calves were restrained and the behaviour of unrestrained animals was ignored in the conclusions drawn from the tests. The relationship between adverse weather and calf mortality is more speculation than documentation yet often has been uncritically cited. In our view, healthy newborn barren-ground caribou are well adapted physiologically and behaviourally to cope with all but the most severe adverse weather.